Joint universality for $L$-functions from Selberg class and periodic Hurwitz zeta-functions - Macaitienė, R. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We obtain a joint universality theorem on the approximation of a collection of analytic functions by a collection of shiftsconsisting of $L$-functions from the Selberg class and periodic Hurwitz zeta-functions.